Smart photochromic fabric prepared via thiol-ene click chemistry for image information storage applications. (September 2021) - Qi, Youguo; Fan, Ji; Chang, Yuqi; Li, Yanjie; Bao, Bingwei; Yan, Bingfei; Li, Hongqi; Cong, Peihong
Abstract: Photochromic materials with reversible optical properties induced by light have always been a research hotspot in the field of optoelectronics. In this work, a novel type of smart photochromic fabric is manufactured by covalent bonding of 3-mercaptopropyltrimethoxysilane (MPTMS) modified cotton fabric and spirooxazine (SO). Based on the established thiol-ene click chemistry principle, the dynamic control of the optical behavior of cotton fabric is realized. The photochromic fabric can change from colorless to blue with a fast light response speed under UV irradiation while presenting good fine images. After 20 reversible color-changing cycles, it still possesses photochromic properties and reusability, which means that the prepared photochromic fabric has great value in smart devices and light detection. Besides, the practical application in the field of optical information storage and information security encryption has been proved via the development of a Quick Response (QR) code security system. Graphical abstract: Image 1 Highlights: A novel thiol-ene click chemistry method was used to prepare a light-responsive smart textile. The prepared cotton fabric exhibits favorable photochromic properties. The photochromic cotton fabric is expected to be used in optical information storage.